Proceedings of the 14th Annual ACM SIGCSE Conference on Innovation and Technology in Computer Science Education 2009
DOI: 10.1145/1562877.1562892
|View full text |Cite
|
Sign up to set email alerts
|

The student view on online peer reviews

Abstract: Peer review is used as an effective quality assurance measure in many contexts, including science, business, programming or education. In education, several studies confirmed the positive effects of peer reviewing on student learning. Based on recent research concerning the role of media in the peer review process this study investigates how students perceive the process, content and effects of peer reviews. We also analyze students' opinions on different modes of peer reviewing activities, e.g. online vs. fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…Bauer et al [1], Hamer et al [3], Orsmond et al [5], Sondergaard [7] have all investigated the drawbacks and benefits of peer reviews in the context of computer science education. These all investigate students' attitude after the review process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bauer et al [1], Hamer et al [3], Orsmond et al [5], Sondergaard [7] have all investigated the drawbacks and benefits of peer reviews in the context of computer science education. These all investigate students' attitude after the review process.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the final grading is done by teachers, which is why we refer to the activity done by students as scoring. 1 We present how we introduced a tool for peer review that supports anonymous scoring of reports, the possibility for students to score received reviews, teacher intervention when disputes occur, and teacher grading of both reviews and reports. Knowing that the students had experience with peer review from a previous course and expressed concerns made us cautious and curious.…”
Section: Introductionmentioning
confidence: 99%
“…Some describe a positive view on peer review (Bauer et al 2009) or seeing it as generally useful (Basnet et al 2010), others report students finding it hardly helpful and are complaining about a lack of effort from their peers (Lu et al 2015), (Nagel & Kotzé 2010), or receiving mostly offensive feedback from their colleagues (Wolfe 2004). Further issues mentioned in related research show some of the reservations students have against reviewing, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Further issues mentioned in related research show some of the reservations students have against reviewing, e.g. that reviewing is teachers' work that makes students uncomfortable (Basnet et al 2010), that some criteria were hard to judge (Bauer et al 2009), that reviewing took time away from other work (Basnet et al 2010), and that reviewing in groups showed instances of social loafing (Turner et al 2011). …”
Section: Related Workmentioning
confidence: 99%
“…As to the benefits of peer review, besides the ones stated above, some authors [7] [5] [6] refer: promotion of active learning [4] and autonomy, increased students' engagement and social interaction, significant increase in the amount of feedback students receive, improvement of skills related to the diagnosis, evaluation, synthesis and professional communication, development of new ideas and critical thinking [29]. At the same time students provide to the peer assessed with external feedback [30], they observe how they solve problems, and learn to think critically.…”
Section: Introductionmentioning
confidence: 99%